Ligand-Driven Advances in Iridium-Catalyzed sp3 C–H Borylation: 2,2′-Dipyridylarylmethane - Jones, Margaret R.; Schley, Nathan D. (Synlett, 2021)
The field of catalytic C–H borylation has grown considerably since its founding, providing a means for the preparation of synthetically versatile organoborane products. Although sp2 C–H borylation methods have found widespread and practical use in organic synthesis, the analogous sp3 C–H borylation reaction remains challenging and has seen limited application. Existing catalysts are often hindered by incomplete consumption of the diboron reagent, poor functional-group tolerance, harsh reaction conditions, and the need for excess or neat substrate. These challenges acutely affect the C–H borylation chemistry of unactivated hydrocarbon substrates, which has lagged in comparison to methods for the C–H borylation of activated compounds. Herein, we discuss recent advances in the sp3 C–H borylation of undirected substrates in the context of two particular challenges: (1) utilization of the diboron reagent and (2) the need for excess or neat substrate. Our recent work on the application of dipyridylarylmethane ligands in sp3 C–H borylation has allowed us to make contributions in this space and has presented an additional ligand scaffold to supplement traditional phenanthroline ligands.
Keywords: C–H borylation; alkanes; iridium; catalysis; ligand effects